2003
DOI: 10.3138/sim.3.4.002
|View full text |Cite
|
Sign up to set email alerts
|

“Live in Your World, Play in Ours”: Race, Video Games, and Consuming the Other

Abstract: As the nascent field of computer games research and games studies develops, one rich area of study will be a semiotic analysis of the tropes, conventions, and ideological sub-texts of various games. This article examines the centrality of race and gender in the narrative, character development, and ideologies of platform video games, paying particular attention to the deployment of stereotypes, the connection between pleasure, fantasy and race, and their link to instruments of power. Video games represent a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
67
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 6 publications
0
67
0
6
Order By: Relevance
“…Furthermore, in games that did include female representation, these were in secondary roles with females portrayed in overly sexualized ways or as victims of aggression (Burgess, Dill, Stermer, Burgess, & Brown, 2011;Dietz, 1998;Dill & Thrill, 2007;Ivory, 2006;Leonard, 2003;Provenzo, 2000;Williams et al, 2009). Additionally other studies have demonstrated the impact of a female avatar's sexualized appearance on acceptance of rape myth and sexism (Fox & Bailenson, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in games that did include female representation, these were in secondary roles with females portrayed in overly sexualized ways or as victims of aggression (Burgess, Dill, Stermer, Burgess, & Brown, 2011;Dietz, 1998;Dill & Thrill, 2007;Ivory, 2006;Leonard, 2003;Provenzo, 2000;Williams et al, 2009). Additionally other studies have demonstrated the impact of a female avatar's sexualized appearance on acceptance of rape myth and sexism (Fox & Bailenson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When exploring previous research on character representation in digital games, there is a key distinction between male and female characters (Leonard, 2003;Thompson & Zerbinos, 1995;Williams, Martins, Consalvo, & Ivory, 2009). For example, within a sample of games studied, Williams et al (2009) found that 40% did not include any female characters.…”
Section: Introductionmentioning
confidence: 99%
“…Whyville offers a particularly promising context in which to examine racial self-representation because it is part of a new genre of virtual worlds that rely heavily on player-generated content. A small number of previous studies have documented racial stereotyping found in the available avatar choices offered within commercial games (Everett, 2005;Leonard, 2003). Because these studies were set in games that had very limited design choices, their focus was not on player agency in self-representation but on the gender and racial stereotypes embedded by professional game designers (Taylor, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Computer games have become the main source of entertainment, rivaling the popularity of movies and TV, for both children and adolescents (Olson, 2010;Spence & Feng, 2010), to the extent that 21st century youth, growing up in the era of videogames, may be called the videogame generation (Bogost, 2007;Leonard, 2003; for the purpose of this paper, the terms ''computer game '' and ''videogame'' are used interchangeably). Although most videogame research has until recently focused on the impact of these games on academic performance and aggression (Lenhart et al, 2008), there is now an increasing interest in understanding the potential of computer games for enhancing cognitive development and learning.…”
Section: Introductionmentioning
confidence: 99%